2009
DOI: 10.1002/bit.22507
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation‐independent community development in low‐temperature anaerobic biological wastewater treatment bioreactors

Abstract: The reproducibility and stability of low- temperature anaerobic wastewater treatment systems undergoing transient perturbations was investigated. Three identical anaerobic expanded granular sludge bed-based bioreactors were used to degrade a volatile fatty acid and glucose-based wastewater under sub-ambient (15 degrees C) conditions. The effect of a variety of environmental perturbations on bioreactor performance was assessed by chemical oxygen demand removal. Temporal microbial community development was monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…If anaerobic wastewater treatment without heating the reactors can be applied to low-strength wastewater, the cost of anaerobic wastewater treatment can be reduced, thereby making this technology an attractive option for the treatment of a variety of wastewater categories. Improvements in reactor design and operational conditions have helped overcome many of the disadvantages of anaerobic wastewater treatment that limited its application to high-strength wastewater treatment at mesophilic or thermophilic temperatures and have allowed for successful operation of anaerobic wastewater treatment reactors at low temperatures (Dhaked et al, 2010;Lettinga et al, 1999;Lettinga et al, 2001;Trzcinski and Stuckey 2010;Luostarinen and Rintala 2005;Madden et al, 2010;Xing et al, 2009;McKeown et al, 2009). In addition, several studies have focused on anaerobic wastewater treatment of low-strength wastewaters at lower temperatures (Elmitwalli et al, 2003;Angenent et al, 2001;Gomec et al, 2008;Matsushige et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…If anaerobic wastewater treatment without heating the reactors can be applied to low-strength wastewater, the cost of anaerobic wastewater treatment can be reduced, thereby making this technology an attractive option for the treatment of a variety of wastewater categories. Improvements in reactor design and operational conditions have helped overcome many of the disadvantages of anaerobic wastewater treatment that limited its application to high-strength wastewater treatment at mesophilic or thermophilic temperatures and have allowed for successful operation of anaerobic wastewater treatment reactors at low temperatures (Dhaked et al, 2010;Lettinga et al, 1999;Lettinga et al, 2001;Trzcinski and Stuckey 2010;Luostarinen and Rintala 2005;Madden et al, 2010;Xing et al, 2009;McKeown et al, 2009). In addition, several studies have focused on anaerobic wastewater treatment of low-strength wastewaters at lower temperatures (Elmitwalli et al, 2003;Angenent et al, 2001;Gomec et al, 2008;Matsushige et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…16S rRNA gene fragments were amplified using the Archaea -specific primer set A751F and UA1204R (Baker et al, 2003), and the Bacteria -specific primer set EB341F and UN517R (Muyzer et al, 1993). PCR-amplification of the archaeal and bacterial 16S rRNA genes was performed as described in detail by Madden et al (2010). Dissimilatory sulfite reductase ß-subunit (dsrB) gene fragments were amplified using dsrB-specific primers DSRp2060F (Geets et al, 2006) and DSR4R (Wagner et al, 1998) to yield a dsrB gene fragment of ~350 bp.…”
Section: Methodsmentioning
confidence: 99%
“…Polyacrylamide gels (8% [w/v]; thickness, 1 mm) with a denaturing gradient consisting of 30–60% urea-formamide for archaeal and dsrB samples, or 30–70% urea-formamide for bacterial samples, were used. DGGE was performed, and bands were excised and re-amplified, as described in detail by Madden et al (2010). PCR amplicons from excised bands were sequenced by MWG (UK) using Sanger sequencing technology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, longterm, low-temperature bioreactor operation may act as a selective enrichment for psychrophilic methanogenic activity from mesophilic inocula. Madden et al (2010) investigated the stability of low-temperature UASBs undergoing transient perturbations using COD removal, while microbial ecology was monitored using DGGE. Gene fingerprinting data indicated that Methanosaeta sp.…”
Section: Operating Temperaturementioning
confidence: 99%